Change and Stasis: The Institutionalisation of Developing Country Mitigation in the International Climate Regime - Prys-Hansen, Miriam; Franz, Benedikt (Diplomacy and statecraft, 2015)
The ability of the parties to the United Nations Framework Convention on Climate Change to negotiate an effective agreement for the post-2020 period is highly dependent on whether developing countries should take on binding mitigation commitments. This analysis combines an historical with a discursive institutionalist perspective to trace the conflict around developing country mitigation that accompanies the climate change regime since its inception. The article shows that early decisions on the subject matter shaped the regime until now. At the same time, the discourse and more recent decisions concerning developing country mitigation indicate gradual changes nevertheless. In particular, the Conferences of the Parties in Bali 2007 and Durban 2011 produced outcomes that changed the institutional architecture of the regime significantly. The development of the climate regime regarding developing country mitigation is hence marked by both periods of change and stasis.